New insights for materials science characterisation using different complementary techniques combined with x-ray absorption spectroscopy - Briois, V.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Carrier, X.; Krafft, J. M.; Jubin, C.; Che, M.; Belin, S.; Villain, F.; Bouamrane, F.; Lucas, H.; Lescouëzec, R.; et al. (IOP Publishing, 2005)
The combination of x-ray absorption spectroscopy (XAS) with UV-Vis and Raman spectroscopies or with Differential Scanning Calorimetry (DSC) has been recently carried out on the D44 beamline of DCI-LURE. The different set-ups used to perform such combinations are described and examples of combined investigations belonging to different field of materials science (coordination chemistry, sol-gel and catalysis) are presented. © Physica Scripta 2005.
Keywords: Catalysis; Differential scanning calorimetry; Raman spectroscopy; X ray absorption spectroscopy; Materials science characterization; Sol-gels